A Modified Brompton Technique for the Treatment of Giant Bulla in Patients with Diffuse Emphysema - Wang, Haifeng; Xu, Zhifei; Gao, Wen (The Thoracic and Cardiovascular Surgeon, 2012)
Four patients with diffuse emphysema and a giant bulla were treated by a modified Brompton technique using a mushroom catheter and low suction. There was no mortality although one patient developed a troublesome pulmonary infection. All the patients had significant symptomatic improvement with a mean dyspnoea index changing from 3.5 before operation to 2.25 afterwards. We concluded that the modified Brompton technique is a safe and simple alternative in treating a giant bulla associated with diffuse emphysema.
Keywords: giant bulla; diffuse emphysema; Brompton technique